2005
DOI: 10.1136/gut.2003.033050
|View full text |Cite
|
Sign up to set email alerts
|

The polymorphism interleukin 8 -251 A/T influences the susceptibility of Helicobacter pylori related gastric diseases in the Japanese population

Abstract: Background: Helicobacter pylori infection is associated with variable clinical outcomes, including gastroduodenal diseases, and genetic factors may be relevant in this process. Aims: We investigated the effects of an interleukin 8 (IL-8) gene polymorphism on the risk of gastroduodenal diseases, the degree of H pylori induced gastritis, and IL-8 gene transcription. Subjects: The study was performed in 244 healthy control subjects and 690 H pylori positive patients with non-cardia gastric cancer, gastric ulcer, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
153
3
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 205 publications
(165 citation statements)
references
References 44 publications
5
153
3
1
Order By: Relevance
“…The heterozygous A/T genotype increased more than twice the risk of GC (OR=2.50, 95% CI: 1.27-4.90; P=0.008). Similar results have been reported by Ohyauchi et al, (2005) who showed that this genotype was more frequent in patients with GC (OR=2.02, 95% CI: 1.37-2.97; P=0.0005). Sarvestani et al (2006) also compared the frequency of IL-8 (rs4073) genotypes between patients with gastritis, peptic ulcer and GC and found a higher prevalence of the A/A genotype in patients with GC compared to those with benign diseases (P=0.013).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The heterozygous A/T genotype increased more than twice the risk of GC (OR=2.50, 95% CI: 1.27-4.90; P=0.008). Similar results have been reported by Ohyauchi et al, (2005) who showed that this genotype was more frequent in patients with GC (OR=2.02, 95% CI: 1.37-2.97; P=0.0005). Sarvestani et al (2006) also compared the frequency of IL-8 (rs4073) genotypes between patients with gastritis, peptic ulcer and GC and found a higher prevalence of the A/A genotype in patients with GC compared to those with benign diseases (P=0.013).…”
Section: Discussionsupporting
confidence: 79%
“…This cytokine is involved in the infl ammatory response to infection with Helicobacter pylori, recruits phagocytes and causes damage to the gastric mucosa by inducing the release of reactive oxygen radicals (Torok et al, 2005;Ohyauchi et al, 2005). Furthermore, studies have shown that IL-8 induces cell proliferation and angiogenesis (Karashima et al, 2003;Taguchi et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymorphisms in pro-inflammatory factors could affect the body's inflammatory response by directly impacting the expression and function of certain inflammatory cytokines. Ohyauchi et al (2005) demonstrated that IL-8 -251 A is associated with higher IL-8 gene transcription and thus we evaluated this polymorphism in NSCLC patients of our population.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated IL-8 levels were associated with disease progression and recurrence in human prostate, breast, lung and gastric cancers (Taguchi et al, 2005;Ahmed et al, 2006;Lurje et al, 2008;Millar et al, 2008). Recently, genetic polymorphisms of the IL-8 gene have been implicated in the susceptibility to a range of cancers, including Colon cancer (Ohyauchi et al, 2005), Gastric cancer (McCarron et al, 2002), Prostrate cancer (Ben et al, 2007) and nasopharyngeal cancer (David et al, 2008). In the backdrop of above cited studies, we hypothesize that the IL-8 promoter SNP which results in higher IL-8 secretion, was associated with increased risk of non small cell lung carcinoma.…”
Section: Lack Of Association Of a Common Polymorphism In The 3' -Utr mentioning
confidence: 99%